A 130 nm wideband fully differential linear low noise amplifier. Issue 9 (September 2015) - Zokaei, Abolfazl; Amirabadi, Amir
Abstract In this paper, a wide-band fully differential linear low noise amplifier (LNA) in a standard 130 nm CMOS process is presented. The LNA utilizes Active Post Distortion (APD) as a voltage combiner that prepares a linear transconductance for enabling harmonic cancellation, which can also mitigate the impedance matching device noise. The impedance matching device is connected to the output transistors to ensure the harmonic cancellation at output node while preserving NF and input return loss at input node. This harmonic cancelation is also APD that guarantees an IIP2 and IIP3 of about 26 dBm and 4 dBm respectively at output node. Operating in a wide bandwidth of about 1.5 GHz from 3.5 to 5 GHz, the LNA obtains a maximum power gain (S21) of about 14 dB, input reverse isolation (S11) and NF of less than -15 dB and 3.9 dB respectively. From a 1 V power supply it dissipates about 21 mW and occupies <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frffzbf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.557×0.567mm2</alternatives> of chip area.